Characterization of de-embedding implementations on GaAs substrates - Manigbas, Ron Joseph G.
De-embedding is a vital step to be undertaken for any on-chip device fabrication. De-embedding moves the calibration plane from the measurement plane to the actual plane of the device. It negates all the parasitic effects that manifest at high frequencies and also it cancels out the effect of the pad interconnects. There are various methods of de-embedding an on-chip device. The project implemented four techniques and compared and contrasted each from the other. The four techniques chosen to be characterized are: Open, Thru-Short, Three-Step and Thru-Reflect-Line (TRL). These techniques were compared with each other to find the method most suited for a semi-insulating Gallium Arsenide (GaAs) substrate. An on-chip inductor and an-chip capacitor were used as the devices under test (DUT). These devices were designed to operate at 2.4 and 5 Ghz. The best technique was recommended to the researcher of National Institute of Physics (NIP) for actual use of their fabricated on-chip devices. Accuracy of the method was of highest priority in choosing the technique to be recommended. Other factors were also taken into account, such as the practicality of the technique and ease of use.